Functionally Graded Material Production and Characterization using the Vertical Separator Molding Technique and the Powder Metallurgy Method - Kayabasi, I.; Sur, G.; Gokkaya, H.; Sun, Y. (Engineering, Technology & Applied Science Research, 2022)
Functionally Graded Materials (FGMs) are advanced customized engineering materials that gradually and continuously change their composition. The current study investigated the production feasibility and some post-production mechanical/physical properties of B4C particle-reinforced (avg. 40µm) AA7075 matrix (avg. 60µm) FGM composites with the vertical separator molding technique using the high-temperature isostatic pressing powder metallurgy method. FGMs produced consist of three (0 – 30 – 60 wt. % B4C) and four (0 – 20 – 40 – 60 wt. % B4C) layers. The powders were mixed in a power blender mixer for 2h and were placed in the mold sections with a vertical separator. The lid was closed, and a pre-pressure of 10Mpa was applied. The FGM green sheet was transferred from the vertical separator mold to the hot work tool steel with a press. In this mold, FGMs were sintered at 560°C for 30 min under a pressure of 325MPa. Microstructural examinations did not reveal any separation or crack formation in the layer transition regions of the FGMs. In addition, a relatively homogeneous B4C reinforcing distribution was observed in the layers with a low reinforcement ratio (wt. 20% and 30%) compared to the other layers. The highest hardness was 170 HBN in one layer of the four-layer FGM containing 40% by weight B4C reinforcement. The highest transverse rupture strength was measured in the test performed from the region with the most reinforcement of the four-layer FGM at 482MPa.